Spondias mombin L.: An Updated Monograph - Maria, Ana Clara Brito; Simões, Thaíse Reis; Ramos, Aline de Souza; Almeida, Maíra Martins Haddad de; Silva, Maria Athana Mpalantinos da; Cruz, Jefferson Diocesano da; Ferreira, José Luiz Pinto; Silva, Jefferson Rocha de Andrade; Amaral, Ana Claudia Fernandes (Pharmacognosy Reviews)
Spondias mombin Linn (Anacardiaceae) is a plant species found from southeastern Mexico to Peru and in the northern of Brazil. Its fruits are known as “cajá miúdo” or “cajá pequeno” in Brazil; in Central America, as “jobo”; as “hogplum” or “yellow mombin” in North America; and as “ciruella amarilla” in Mexico and Ecuador, among others. It is used by the local population to treat diseases due to its many biological properties, such as antiviral, anti-inflammatory, antioxidant, and antibacterial properties. This study was carried out using databases, indexed articles, theses, dissertations, and books. These surveys indicate important microscopic and macroscopic patterns of the species. Some studies also confirmed the popular use of S. mombin, showing in vitro and in vivo antioxidant properties and some activities, such as mosquito adulticidal, anti-inflammatory, antiviral, antibacterial, and anthelminthic activities. These properties are attributed to the abundant presence of phenolic compounds. Saponins, alkaloids, phenolic acids, tannins, and flavonoids are also found in its extracts. The results obtained in this study show several pharmacological applications that can lead to the develop ment of new products and drugs based on the properties of S. mombin, which have already been reflected in field patents.
Keywords: Anacardiaceae; Botanical description; Chemical composition; Pharmacology; Phytochemical analysis